Pengukuran Keberhasilan E-Learning dengan Mengadopsi Model Delone & Mclean - ., Deny; Andry, Johanes Fernandes (Universitas Diponegoro, 2018)
Investment resources, time and cost in the implementation of information systems are not small, making measuring the success of information systems becomes very important to do. Meanwhile, the university as an educational institution today has been rampant to implement e-learning as an information system that provides added value for students. A University in North Jakarta has implemented e-learning integrated with information portal of students and lecturers since 2009. But until now has not been measured the success of the information system. So this research is done with one of the goals to measure the success of e-learning adopted by the University. In addition, this research would like to test the success model of DeLone and McLean's updated information system (2003) in the case of e-learning. The analysis was performed using SEM with the help of Lisrel 8.7 which tested 7 hypotheses. From this research found that DeLone and McLean model can not be used to explain the cause of success of e-learning system that its use is required, but need further research to get better level of generalization.